ANALISIS PERGESERAN NILAI TRADISI MAPPATABE PERSPEKTIF SILA KEDUA PANCASILA PADA GENERASI MUDA DI DESA PEMUSIRAN KECAMATAN NIPAH PANJANG KABUPATEN TANJUNG JABUNG TIMUR - Mutmainnah, Wardatul; Melisa; Aditya Candra, Alif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Mappatabe tradition is a local wisdom of the Bugis people, embodying the values ​​of respect, courtesy, and ethics in social life. These values ​​align with the Second Principle of Pancasila, namely "Just and Civilized Humanity." However, developments marked by modernization and globalization have brought changes in the mindsets and behaviors of the younger generation, potentially leading to a shift in cultural values, including in the practice of the Mappatabe tradition. This study aims to analyze the shift in Mappatabe traditional values ​​among the younger generation in Pemusiran Village, Nipah Panjang District, East Tanjung Jabung Regency, and examine their relevance to the values ​​of the Second Principle of Pancasila. This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, interviews, and documentation, involving traditional leaders, community members, and the younger generation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate a shift in values ​​within the Mappatabe tradition, characterized by a decline in the understanding and application of the values ​​of respect, courtesy, and social ethics among the younger generation. This shift is influenced by factors such as modernization, globalization, and the suboptimal process of cultural inheritance. Researchers are analyzing the impact of this shift in tradition.